Frontal Hemodynamic Responses to High Frequency Yoga Breathing in Schizophrenia: A Functional Near-Infrared Spectroscopy Study - Bhargav, Hemant; BN, Gangadhar; Raghuram, Nagarathna; HR, Nagendra (Frontiers in Psychiatry, 2014)
Frontal hemodynamic responses to high frequency yoga breathing technique - Kapalabhati (KB) was compared between patients of schizophrenia (n =18; 14 males, 4 females) and age-gender and education matched healthy subjects (n=18; 14 males, 4 females) using functional near-infrared spectroscopy (fNIRS). The diagnosis was confirmed by a psychiatrist using DSM IV. All patients except one received atypical anti-psychotics (one was on typical). They had obtained a stabilized state as evidenced by a steady unchanged medication from their psychiatrist for past 3 months or longer. They learned KB, among other yoga procedures, in the yoga retreat. KB was practiced at the rate of 120 times per minute for 1minute (min). Healthy subjects who were freshly learning yoga too were taught KB. Both the groups had no previous exposure to KB practice and the training was achieved over 2 weeks. A chest pressure transducer was used to monitor the frequency and intensity of the practice objectively. The frontal hemodynamic response in terms of the oxygenated hemoglobin (oxyHb), deoxygenated hemoglobin (deoxyHb) and total hemoglobin or blood volume (totalHb) concentration was tapped for 5 min before, 1min during and for 5 min after KB. This was obtained in quiet room using a 16 channel functional near-infrared system (FNIR100-ACK-W, BIOPAC Systems, Inc, USA). Average of the eight channels for each side (right and left frontals) was obtained for the three sessions. The changes in the levels of oxyHb, deoxyHb and blood volume for the three sessions were compared between the two groups using Independent samples t test. Within group comparison showed that increase in bilateral oxyHb and totalHb from the baseline was highly significant in healthy controls during KB (right oxyHb, p = 0.00; left oxyHb, p= 0.00 and right totalHb, p = 0.01; left totalHb, p = 0.00), whereas schizophrenia patients did not show any significant changes in the same on both the sides. On the other hand, schizophrenia pat